1996
DOI: 10.1097/00004836-199606000-00016
|View full text |Cite
|
Sign up to set email alerts
|

How to Achieve a Near 100% Cure Rate for H. Pylori Infection in Peptic Ulcer Patients

Abstract: Infection with Helicobacter pylori is the main etiological factor in duodenal and gastric ulcer disease, and eradication of the organism cures peptic ulcer disease. Cure of the infection therefore has become the ultimate treatment goal in ulcer patients. Only therapies that achieve a > 90% cure rate should be used in clinical practice and, as in any other disease, the therapy with the highest cure rates should be used. Bismuth-based triple therapy is considered the gold standard; it has been used successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 19 publications
2
32
0
Order By: Relevance
“…The adherence to both regimens was excellent (92.6% vs 94.4%, p=0.593). Our results are consistent with the notion that pretreatment counselling is very important for good success in H. pylori eradication 26 27…”
Section: Discussionsupporting
confidence: 92%
“…The adherence to both regimens was excellent (92.6% vs 94.4%, p=0.593). Our results are consistent with the notion that pretreatment counselling is very important for good success in H. pylori eradication 26 27…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that quadruple therapy consisting of a similar combination of antibiotics and a proton-pump inhibitor has repeatedly been shown to be equally eff ective in spite of the presence of metronidazole resistance when the attention was given to the dose of metronidazole (e.g. 400 or 500 mg three times daily) and duration of therapy of approximately 14 days [47][48][49][50][51][52]. So, metronidazole-containing quadruple therapy may have overcome metronidazole resistance to some degree in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…de Boer who performed many of the initial Dutch trials examining dose, duration and the use of PPI's, used a 7-point approach of patient education/motivation starting with taking time to talk to the patient and explain the rationale. He then went on to explain the potential difficulties and side effects that might occur and provided details about how to take the medications 45 . He and Borody had good but not perfect adherence.…”
Section: Adherence (Compliance) With Bismuth Quadruple Therapymentioning
confidence: 99%